Influence of movement deviation on metabolic economy of the v1 and v2 cross-country skate techniques - Moore, S. R.; Weich, C.; Torchia, I.; Jensen, R. L. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
As cross-country skiers progress to elite competition levels, the quality of sport-specific training becomes an important component to achieving performance-enhancing physiological adaptations (Sandbakk & Holmberg, 2017). Although the maximal rate of oxygen consumption (VO2max; ml/kg*min) is a traditional measure used to indicate the aerobic capacity of endurance athletes, there appears to be only a marginal amount of improvement obtainable in the aerobic capacities of highly trained athletes (Sandbakk & Holmberg, 2017). Instead, optimizing the energy cost and efficiency of competition techniques and speeds could be a more effective goal of sport-specific training. Economical movement during submaximal efforts (i.e. race pace at 80-90% VO2max) is not related to high peak oxygen uptake (VO2peak; ml/kg*min). Ainegren et al. (2013) found that recreational skiers utilize a greater relative oxygen uptake (VO2; ml/kg*min) and percentage of VO2peak to accomplish a roller-ski task of equivalent workload compared to senior elite skiers. Furthermore, VO2 of roller skiing at a standardized pace has been positively correlated with performance via national ski association scores using three skate-skiing techniques (r= 0.62 - 0.72; Millet et al., 2003). Although Carlsson et al. (2014) did not detect group differences in economy between small samples sizes of world d a s s and national level skiers, lower metabolic rates (i.e. anaerobic and aerobic components) were detected in a less elite group. Thus, development of economical movement patterns appears to be a principal determinant of race performance. The unique kinematic requirements of the skate cycle necessitate technique-specific precision and coordination for effective movement. The V1- and V2-skates are two commonly used techniques that are associated with the economic cost of Nordic skiing (Kvamme et al., 2005). The V1-skate, characterized by an asymmetrical (offset) pole plant, is commonly used on uphill terrain, while the V2-skate is used for powerful surges on flats and moderate or short hills (Kvamme et al., 2005). Interestingly, the V2 technique appears more metabolically costly than the V1 when skating on flats (Millet et al., 2003) and with increasing slopes (Kvamme et al., 2005). This may be explained bygreaterVI-upper body efficiency (Millet et al., 2003; Milletet al., 1998b), increased arm recovery times (Millet et al., 1998b; Millet et al., 1998a), and more effective cycle length-to-rate ratios (Stöggl et al., 2018). Thus, technique-specific training and strength may also influence V1 and V2 performance due to the effectiveness of the propulsive pole plant (DuVall et al., 2019; Sandbakk & Holmberg, 2014). Ultimately, the disparity in the metabolic cost of these skate techniques has potential to affect competitive skiing performance. The purpose of the current study was threefold; (i) to determine if significant differences exist in economy and movement variability between the V1- and V2-skate techniques in elite cross-country skiers; (ii) to determine the effects on economy and movement incurred by a V1 and V2 technique-specific training period; (iii) to determine if a relationship exists between the economic cost and variability of movement of the V1 and V2 techniques.